CLOVER: The CMB polarization observer - Maffei B.; Ade P. A. R.; Calderon C.; Challinor A. D.; De Bernardis P.; Dunlop L.; Gear W. K.; Giraud-Heraud Y.; Goldie D. J.; Grainge K. J. B.; Isaak K. G.; Johnson B.; et al. (2005)
We present a new, fully-funded ground-based instrument designed to measure the B-mode polarization of the Cosmic Microwave Background (CMB). The concept is based on three independent sub-systems operating at 90, 150 and 220 GHz, each comprising a telescope and a focal plane of horn-coupled background-limited bolometers. This highly-sensitive experiment, planned to be based at Dome C station in Antarctica, is optimised to produce very low systematic effects. It will allow the detection of the CMB polarization over angular multipoles 20 < l < 1000 accurately enough to measure the B-mode signature from gravitational waves to a lensing-confusion-limited tensor-to-scalar ratio r ∼ 0.005. © EAS, EDP Sciences 2005.